Competency model for science and technology (S&T) personnel for the iron and steel industry - A. Kozhevnikov (Metalurgija, 2018)
The article presents the competency model for S&T personnel for the iron and steel industry. The study performed has made it possible to determine a cluster of competencies required for innovative development of production involving development of energy-efficient technologies and high-performance steels. The results of the performed analysis have shown that for highly qualified professionals it is not sufficient just to have professional knowledge and demonstrate personal efficiency and ability to work in a team. They should also have professional engineering excellence skills, management skills and should be innovation-focused.